Documentary evidence and the production of power in medieval Nubia - Giovanni R. Ruffini (Afriques)
Documents from Qasr Ibrim in northern Nubia reveal the administrative and legal practices of medieval Africa. The land sales provide direct glimpses into the activity of the eparch of Nobadia, the region’s highest political official, who was active in the region’s private land market. The accounts suggest the existence in northern Nubia of a cash economy and a gold-to-silver exchange rate identical to that of Muslim Egypt. The personal correspondence hints at power struggles between Nubia’s center and its periphery. This evidence is not an accident or a side-effect. It is a deliberate feature of the texts themselves. Nubian correspondence includes suggestions of insubordination and shows high officials attempting to re-establish their power at a distance. Some documents include explicit challenges to other texts, or defensive measures protecting a text against accusations of falsehood. In this way, the texts become weapons in an ongoing struggle. In short, documentary production in medieval Nubia was neither economically nor politically neutral. Nubia’s elite needed its documentary evidence to construct its power.